Electrocatalytic Reduction of O2 by ITO-IrOx: Implication for Dissolved Oxygen Sensor in the Alkaline Medium - Munira Siddika; Md. Mahmudul Hasan; Tahamida A. Oyshi; Mohammad A. Hasnat (Electrochem, 2023)
Water pollution has badly affected human health, aquatic life, and the ecosystem. The purity of surface water can be measured in terms of dissolved oxygen (DO) measurements. Hence, it is desirable to have a portable and simple-to-use dissolved oxygen sensor. One possible remedy is an electrochemical sensor. Thus, we proposed an ITO-IrOx electrocatalyst for an effective and interference-free DO sensor utilizing the principle of oxygen reduction reaction (ORR). The ITO-IrOx was characterized using cyclic voltammetry (CV), scanning electron microscopy (SEM), electrochemical impedance spectrometry (EIS), X-ray photoelectron spectroscopy (XPS), and reflectance spectroscopy-based techniques. Reflectance spectra of the ITO-IrOx electrode showed the photoresist capability. The EIS spectra revealed lower charge transfer resistance for the ITO-IrOx electrode in ORR. The IrOx film on ITO exhibited a quick (one electron, α = 1.00), and reversible electron transfer mechanism. The electrode demonstrated high stability for oxygen sensing, having a limit of detection (LOD) of 0.49 ppm and interference-free from some common ions (nitrate, sulphate, chloride etc.) found in water.